How to Measure Leaf Disease Damage Using Image Analysis in ImageJ - Lillian Pride; Gary Vallad; Shinsuke Agehara (EDIS)
This new 13-page article introduces simple image processing and analysis techniques to quantify leaf disease damage using ImageJ, an open-source image processing program. These techniques are not meant to replace crop scouting or disease diagnosis by a plant diagnostic laboratory, but rather to provide a supplemental tool for making quantitative measurements of leaf disease damage. Similar techniques are also available for plant growth assessment, including plant height, plant width, and canopy cover area. The image processing and analysis techniques introduced in this article are fairly simple to use and thus can be adopted not only by researchers, but also by producers, crop consultants, Extension agents, and students. Written by Lillian Pride, Gary Vallad, and Shinsuke Agehara, and published by the UF/IFAS Horticultural Sciences Department. https://edis.ifas.ufl.edu/hs1382